Virtual idol and youth identity: the impact of mainstream culture on the virtual idol online fanbase community in China - Song, Liuyan; Chow, Ow Wei; Na, Mingyu; Sarjit, S. Gill (Redfame Publishing Inc., 2024)
Virtual idols originated in Japan and are mainly composed of singing synthesizers, virtual reality technology, and ACG (anime-comics-games) cultural elements, which is a subcultural phenomenon. In recent years, the growing fanbase of virtual idols has attracted the attention of mainstream media and government in China. The state media in China have used virtual idols as a medium to promote mainstream culture to Chinese young people, and influence fans' youth identity by injecting mainstream culture into virtual idols' musical works, stage performances, and public opinion propaganda. This research will use a virtual ethnographic approach to explore the impact of the mainstreaming of virtual idols and their music on online fanbase communities. The study concludes that under the influence of mainstream culture, virtual idol subculture in China has gradually become mainstream, and its fanbase has also experienced a transformation from post-subcultural group identity to national identity. This study provides new insights into the musical phenomenon of the mainstreaming of virtual idols in China from the perspective of post-subculture theory and identity.